Evaluation of Albumin Utilization in a Major Teaching Hospital in Iran Before and After Guideline Implementation - Shahriyar Shahbazi Khamas; Iman Mirbagheri; Anoush Dehnadi Moghadam; Atefeh Jafari; Asieh Ashouri (Journal of Pharmaceutical Care, 2021)
Background: Inappropriate use of drugs is one of the major issues in health care system. Rational drug utilization based on the appropriate guidelines has an important role in management of use of expensive medications. We aimed to evaluate albumin usage's appropriateness based on evidence-based indications before and after implementing albumin prescription guideline in a teaching hospital.Methods: This study was performed in two phases. During two-month periods, all the patients who were ordered to receive albumin were evaluated. The first phase was done in November and December of 2017, during which, based on physicians' comments, the guideline was finalized and then implemented. Phase two was performed in May and June 2018.Results: Albumin was prescribed appropriately in 33 patients (55%) in the first phase and 43 (70%) patients in the second phase. 299 vials in the first phase and 456 vials in the second phase were prescribed which 198 vials (66%) and 394 (86%) vials were used with appropriate indications, respectively. The number of vials consumed with inappropriate indication decreased significantly from 101 vials (34%) in the first phase to 62 vials (14%) in the second phase (P-value=0.01). The average cost of the inappropriate indication per patient decreased from $197.3 ± 131.6 in the first phase to $183.5 ± 126.8 in the second phase (P-value=0.52).Conclusion: This study showed implementing a DUE program and designing a guideline for rational prescribing of albumin and interventional methods can optimize treatment duration, significantly decrease inappropriate usage, and avoid unnecessary hospital costs.